The Endoplasmic Reticulum Glucosyltransferase Recognizes Nearly Native Glycoprotein Folding Intermediates - Caramelo, Julio Javier (2004)
The UDP-Glc:glycoprotein glucosyltransferase (GT), a key player in the endoplasmic reticulum (ER) quality control of glycoprotein folding, only glucosylates glycoproteins displaying non-native conformations. To determine whether GT recognizes folding intermediates or irreparably misfolded species with nearly native structures, we generated and tested as GT substrates neoglycoprotein fragments derived from chymotrypsin inhibitor 2 (GCI2) bearing from 53 to 64 (full-length) amino acids. Fragment conformations mimicked the last stage-folding structures adopted by a glycoprotein entering the ER lumen. GT catalytic efficiency (V(max)/K(m)) remained constant from GCI2-(1-53) to GCI2-(1-58) and then steadily declined to reach a minimal value with GCI2-(1-64). The same parameter showed a direct hyperbolic relationship with solvent accessibility of the single Trp residue but only in fragments exposing hydrophobic amino acid patches. Mutations introduced (GCI2-(1-63)V63S and GCI2-(1-64)V63S) produced slight structural destabilizations but increased GT catalytic efficiency. This parameter presented an inverse exponential relationship with the free energy of unfolding of canonical and mutant fragments. Moreover, the catalytic efficiency showed a linear relationship with the fraction of unfolded species in water. It was concluded that the GT-derived quality control may be operative with nearly native conformers and that no alternative ER-retaining mechanisms are required when glycoproteins approach their proper folding.